Socioeconomic school segregation in a market-oriented educational system. The case of Chile - Valenzuela, Juan Pablo; Bellei, Cristian; Ríos, Danae de los (Journal of education policy, 2014)
This paper presents an empirical analysis of the socioeconomic status (SES) school segregation in Chile, whose educational system is regarded as an extreme case of a market-oriented education. The study estimated the magnitude and evolution of the SES segregation of schools at both national and local levels, and it studied the relationship between some local educational market dynamics and the observed magnitude of SES school segregation at municipal level. The main findings were: first, the magnitude of the SES segregation of both low-SES and high-SES students in Chile was very high (Duncan Index ranged from 0.50 to 0.60 in 2008); second, during the last decade, SES school segregation tended to slightly increase in Chile, especially in high schools (both public and private schools); third, private schools - including voucher schools - were more segregated than public schools for both low-SES and high-SES students; and finally, some market dynamics operating in the Chilean education (like privatization, school choice, and fee-paying) accounted for a relevant proportion of the observed variation in SES school segregation at municipal level. These findings are analyzed from an educational policy perspective in which the link between SES school segregation and market-oriented mechanisms in education plays a fundamental role.